2019
DOI: 10.1021/acs.jafc.9b05794
|View full text |Cite
|
Sign up to set email alerts
|

Correction to Evaluation of the Perceptual Interaction among Sulfur Compounds in Mango by Feller’s Additive Model, Odor Activity Value, and Vector Model

Abstract: P age 8937. An incorrect reference was provided in the original publication for ref 46. The correct reference is given below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Ethyl caproate and methyl caproate were important flavor substances of Chinese bacon, which could impart a pleasant fruity aroma [29] . The present study showed that this content in the ultrasonic treatment group was significantly lower than in the CK group.…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl caproate and methyl caproate were important flavor substances of Chinese bacon, which could impart a pleasant fruity aroma [29] . The present study showed that this content in the ultrasonic treatment group was significantly lower than in the CK group.…”
Section: Resultsmentioning
confidence: 99%